Treatment of Craniodiaphyseal Dysplasia Presenting with Chiari Type-I - Özay, Rafet; Doruk, Ebru Doğan; Balkan, Mehmet Serdar; Ergüngör, Mehmet Fikret (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2016)
Objective Chiari malformation type-I (CM-1) is described radiographically as a simple displacement of the cerebellar tonsils at least 5 mm below the foramen magnum (FM). If CM-1 exists due to hyperostosis of the cranial bones, the authors were not able to determine a common consensus for the treatment of CM-1 and syringomyelia.Methods A 31-year-old-female presented to our hospital with bilateral facial paralysis, hypoesthesia and motor loss of the extremities. The patient had bilateral gag reflex loss, phonation disorder and dysarthric speaking. Sensory and motor deficits were available at the bilateral upper and lower extremities. The skeletal radiographs revealed extensive thickening and sclerosis of the calvarial and facial bones, moderate widening and sclerosis of the clavicles and ribs, and that the internal auditory canal (IAC) and the optic foramen (OF) were narrowed. CM-1 and syringomyelia secondary to the small posterior fossa were due to calvarial hyperostosis. The patient underwent posterior fossa decompression and duraplasty. In addition, a syringosubarachnoid shunt was placed at the level of C7-T1. The symptoms of lower cranial nerve palsy and motor loss were recovered, but the symptoms of the foraminal stenosis, such as visual and auditory losses and facial paralysis were not recovered in any way.Conclusion We described in this case report CM-1 as a late complication of craniodiaphyseal dysplasia (CDD), and the difficulties in its treatment. In the treatment of these patients with CDD, posterior fossa decompression and syringosubarachnoid shunting are necessary, in spite of all the risks of these procedures.
Keywords: skull; hyperostosis; dysplasia; syringomyelia; craniectomy; decompression